Web-scale discovery and Google Scholar: A study in use patterns. Issue 1 (2nd March 2020) - Wang, Ya
Abstract: J. Paul Leonard Library at San Francisco State University launched a web-scale discovery service, branded as OneSearch in 2013. Before that, Leonard library had been using Google Scholar since 2006. This study gathered usage data on OneSearch and Google Scholar from the library OpenURL link resolver, SFX, and the interlibrary loan server, ILLiad, from 2011 to 2017. The findings demonstrated that OneSearch had become an essential library search tool, especially among students. Data revealed fewer patrons used Google Scholar after the implementation of OneSearch. However, Google Scholar remained an important research tool that complemented OneSearch.